Mutual-Information-Based Adaptive Bit-Loading Algorithms for LDPC-Coded OFDM - Yan Li; Ryan, W.E. (IEEE transactions on wireless communications, 2007)
In this paper we analyze the performance of an LDPC-coded OFDM system with adaptive bit-loading based on mutual information. We demonstrate that the mutual information between the transmitted binary sequence and the soft information input to LDPC decoder well characterizes the performance of the LDPC-coded system, independent of the modulation type and the number of carriers. We design mutual information-based adaptive bit-loading and power allocation algorithms for LDPC-coded OFDM systems to maximize throughput performance under a packet-error rate constraint. To characterize the performance of the system under study, we derive the achievable information rate and a throughput upper bound for the system